2013
DOI: 10.1139/er-2012-0036
|View full text |Cite
|
Sign up to set email alerts
|

Plant phenological modeling and its application in global climate change research: overview and future challenges

Abstract: Plants interact to the seasonality of their environments, and changes in plant phenology have long been regarded as sensitive indicators of climatic change. Plant phenology modeling has been shown to be the simplest and most useful tool to assess phenol–climate shifts. Temperature, solar radiation, and water availability are assumed to be the key factors that control plant phenology. Statistical, mechanistic, and theoretical approaches have often been used for the parameterization of plant phenology models. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 141 publications
(189 reference statements)
0
72
0
Order By: Relevance
“…Vegetation phenology is a fundamental determinant affecting the processes of carbon, water, and energy exchange in wetland ecosystems [6,7]. Phenology determines the timing and duration of the photosynthetically active canopy and drives annual carbon uptake in wetland ecosystems [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation phenology is a fundamental determinant affecting the processes of carbon, water, and energy exchange in wetland ecosystems [6,7]. Phenology determines the timing and duration of the photosynthetically active canopy and drives annual carbon uptake in wetland ecosystems [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [1] also showed that the onset of the growing season was significantly correlated with the spring temperatures in the circumpolar and circumboreal areas. So far, there are three types of approaches for detecting the start of the growing season for vegetation [18]: (a) the conventional phenology approach observing the phenology of individual plants or tree stands [12,13,17,19]; (b) the land surface phenology approach using satellite-derived growing season metrics retrieved from various vegetation index data, such as the Normalized Difference Vegetation Index (NDVI) data from, e.g., the Advanced Very High Resolution Radiometer (AVHRR) and Moderate Resolution Imaging Spectroradiometer (MODIS) [9,[20][21][22]; (c) temperature, solar radiation and water availability are assumed to be the key factors that control plant phenology. Statistical, mechanistic and theoretical approaches have often been used for the parameterization of plant phenology models describing the response to these key factors [18].…”
Section: Introductionmentioning
confidence: 99%
“…Because genotypes differ measurably in environmental sensitivities, different model parameterizations can represent allelic variation in how organisms respond to diverse environmental factors (Morin et al 2007;Wilczek et al 2009;Zhao et al 2013). As such, this modeling approach supplies an extremely flexible tool for predicting the reaction norms of particular genotypes in response to complex and variable environments (Buckley and Kingsolver 2012).…”
mentioning
confidence: 99%